Sickle cell nephropathy - Hariri, Essa (2018)
Sickle cell nephropathy is a major complication of sickle cell disease. It manifests in different forms, including glomerulopathy, proteinuria, hematuria, and tubular defects, and frequently results in end-stage renal disease (ESRD). Different pathophysiologic mechanisms have been proposed to explain the development of nephropathy in SCD, where hemolysis and vascular occlusion are the main contributors in the manifestations of this disease. Markers of renal injury, such as proteinuria and tubular dysfunction, have been associated with outcomes among patients with sickle cell nephropathy and provide means for early detection of nephropathy and screening prior to progression to renal failure. In small-sized clinical trials, hydroxyurea has demonstrated to be effective in slowing the progression to ESRD. Dialysis and renal transplantation represent the last resort for patients with sickle cell nephropathy. Nevertheless, despite the availability of diagnostic and therapeutic strategies, sickle cell nephropathy remains a challenging and under-recognized complication for patients with sickle cell disease.